Pengaruh Kepemilikan Manajerial, Profitabilitas, Terhadap Kebijakan Hutang Pada Perusahaan Consumer Goods Yang Terdaftar di Bursa Efek Indonesia Selama Periode 2018-2021 - Ranji Mai Putra; Muhammad Rivandi (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Debt policy basically depends on community development where the development of a company plays an important role to support the ability to use debt in business finance. This study aims to determine the effect of managerial ownership, profitability on debt policy. The research population is consumer goods sector companies. The research sample is 11 companies selected using a purposive sampling technique with an observation period of 2018-2021. The data analysis method used in this research is the penel data regression model. Based on the results of testing managerial ownership has no effect on debt policy and profitability has a significant positive effect on debt policy.